2012
DOI: 10.1007/s13566-012-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation prophylaxis as primary prevention of heterotopic ossification of the knee: classification of disease and indications for treatment

Abstract: Objective Heterotopic ossification (HO) of the knee joint is seen in up to 42 % of patients following total knee arthroplasty (TKA). Despite this prevalence, there is a paucity of data to validate the efficacy and after effects of prophylactic radiotherapy (PRT) to the knee to prevent HO. We report retrospectively our institution's experience with 12 patients treated with PRT of the knee joint. We also present a classification scheme and review the indications for PRT following TKA. Methods Between 1999 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Overall, there were no toxicities, acute or late, noted. One report from Drexel University with 12 patients who underwent RT for knee HO prophylaxis had no HO recurrence after treatment [8]. This patient group differed from ours as 8 (61.5%) of our patients versus none of their patients had evidence of HO prior to surgery.…”
Section: Radiation Therapy (Rt) For Prophylaxis Of Heterotopic Ossificontrasting
confidence: 59%
See 1 more Smart Citation
“…Overall, there were no toxicities, acute or late, noted. One report from Drexel University with 12 patients who underwent RT for knee HO prophylaxis had no HO recurrence after treatment [8]. This patient group differed from ours as 8 (61.5%) of our patients versus none of their patients had evidence of HO prior to surgery.…”
Section: Radiation Therapy (Rt) For Prophylaxis Of Heterotopic Ossificontrasting
confidence: 59%
“…There are multiple case reports and a retrospective study with 12 patients [8]- [15]. The development of HO has been noted after total knee arthroplasty in up to approximately 40% of patients [9] [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first published cases on HO prophylaxis of the knee is by Lo et al, who reported successful radiation prophylaxis with 7 Gy after revision TKA in a patient who developed symptomatic HO following initial TKA [ 16 ]. Subsequent studies reported no recurrence of HO with 7 Gy of postoperative radiation in high-risk patients and those who underwent HO excision [ 6 , 17 ]. Some studies have proposed non-steroidal anti-inflammatory drug use as attributing factors to the low incidence of HO after TKA [ 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%